Penanaman Nilai-nilai Pendidikan Karakter Anak Usia Dini Melalui Kegiatan Read Aloud - Yudelnilastia, Yudelnilastia; Zulmuqim, Zulmuqim; Rehani, Rehani (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2023)
Character education is an effort to help the development of a child's soul, both physically and mentally, from his nature to a better human civilization. The focus of this research is 1) How to implement character education in early childhood through read-aloud activities in the Sumbar Membacakan Nyaring community? 2) What are the supporting and inhibiting factors in character education in early childhood in the Sumbar. Membacakan Nyaring community? The research method used is a qualitative description, with data collection techniques through interviews, observation, and study documents. The data analysis techniques carried out are: 1) Data reduction 2) Data display; 3) Verification and 4) conclusion drawing. Results are: 1) The implementation of character education carried out by families through read-aloud activities has four stages, namely: the preparation stage, the initial stage, the stage during the activity and the stage after the activity; 2) Supporting factors are: the presence of story books equipped with interesting pictures for early childhood, as well as story topics that contain character values that are appropriate to early childhood cognitive development; The inhibiting factor is the busyness of parents because of work outside the home and other family members are less supportive in terms of setting an example.